Strategi Peningkatan Pelayanan Administrasi Kependudukan Berbasis SWOT di Desa Cimekar Kabupaten Bandung - Mardiana, Silvi Syahrani; Shalshabilla, Shalma; Yuningsih, Neneng Yani (Innovative: Journal Of Social Science Research, 2025)
Villages as the foremost unit of government have a strategic role in ensuring the fulfillment of community civil rights, especially through population administration services such as ID cards and family cards. However, Cimekar Village, Kabupaten Bandung, still faces a number of problems, including the unavailability of an Anjungan Dukcapil Mandiri (ADM) machine, as well as social problems such as marriages and divorces that are not legally recorded. This research aims to formulate a strategy to improve civil registration services in Cimekar Village, Bandung Regency, through a SWOT analysis approach. The method in this research uses a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. Based on the research results through the SWOT analysis approach, it shows that Cimekar Village has strengths in organizational structure, apparatus responsiveness, and information openness, but is also faced with technical weaknesses and social threats. The proposed strategies include developing digital services (SO strategy), media-based legal education (ST strategy), mobile service cooperation (WO strategy), and legal data collection and socialization programs (WT strategy).